The Effect of Coastal Environment-Based Project-Based Learning Model on the Science Literacy Skills of Elementary School Students at SD Negeri 127 in South Halmahera - Rusly, Nasrullah; Toge, Saidi; Tualeka, Erwin (Peneliti.net, 2025)
This study aims to analyze the effect of implementing a coastal environment-based Project-Based Learning (PjBL) model on improving the science literacy skills of elementary school students in South Halmahera Regency. The background of this research stems from the low level of science literacy among elementary school students, particularly in connecting scientific concepts with real-life phenomena around them. South Halmahera, as an archipelagic region, possesses a rich coastal and marine ecosystem that has not yet been optimally utilized as a contextual learning resource. The PjBL model allows students to learn through active involvement in real-life projects relevant to their everyday experiences, which is expected to enhance their motivation, conceptual understanding, and application of science. The method used in this research is a quasi-experimental design with a pretest-posttest control group. The study involved two fifth-grade classes from public elementary schools located in coastal areas, purposively selected based on similar socio-academic conditions. One class was designated as the experimental group, receiving instruction through the coastal-based PjBL model, while the other served as the control group using conventional teaching methods. Projects conducted by the experimental group included creating mangrove ecosystem models, organizing coastal conservation campaigns, and compiling science booklets on local marine biodiversity. The research instrument consisted of a science literacy test that measured three main indicators: (1) the ability to explain scientific phenomena, (2) the ability to design and evaluate scientific investigations, and (3) the ability to interpret data and scientific evidence. Data were analyzed using t-tests to assess differences in score improvement between the experimental and control groups. The results indicated a significant improvement in the science literacy skills of students in the experimental group compared to the control group. The average science literacy score increased by 27.3 points in the experimental group, whereas the control group saw an increase of only 10.4 points. These findings were supported by observations and interviews, which revealed increased student enthusiasm, active involvement in projects, and heightened awareness of local environmental issues. Thus, it can be concluded that the implementation of a Project-Based Learning model based on the coastal environment has proven to be effective in improving the science literacy of elementary school students. The findings of this study highlight the importance of developing curricula based on local potential and providing teacher training to integrate contextual learning approaches in order to enhance the quality of elementary science education, particularly in archipelagic regions such as South Halmahera.